Teacher-oriented culture as correlate of teachers’ service delivery in public secondary schools in Anambra State Nigeria - Samuel Ogechukwu Otugo; Choice Chimaa Okaforcha (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
Teachers’ service delivery in public secondary schools in Anambra State faces challenges such as low morale and weak commitment, often linked to unsupportive school cultures. Emphasizing teacher-oriented culture may enhance motivation, instructional effectiveness, and overall educational outcomes. The study adopted a correlational research design to examine the relationship between school administrative practices, organizational culture, and teachers’ service delivery in public secondary schools in Anambra State, Nigeria. The population comprised 6,598 teachers across six education zones, from which a sample of 660 teachers was selected using multistage sampling techniques. Data were collected using three validated and reliable questionnaires on administrative practices, organizational culture, and service delivery. Pearson Product Moment Correlation Coefficient was used for data analysis at the 0.05 significance level with SPSS. The results examined the relationship between teacher-oriented culture and teachers’ service delivery in public secondary schools in Anambra State. Analysis based on a sample of teachers (618) showed a very strong positive correlation between the two variables, with a correlation coefficient of (r = 0.864). This indicates that improvements in teacher-oriented culture are strongly associated with enhanced teachers’ service delivery. The hypothesis test further revealed that the correlation was statistically significant, as the obtained p-value (0.000) was lower than the level of significance (0.05). Consequently, the null hypothesis was rejected, confirming a significant strong positive relationship between teacher-oriented culture and teachers’ service delivery. The study concludes that teacher-oriented culture plays a significant role in enhancing teachers’ service delivery in public secondary schools in Anambra State. Strengthening teacher-oriented cultural practices is essential for improving instructional effectiveness and achieving educational objectives.